1984
DOI: 10.1126/science.6089348
|View full text |Cite
|
Sign up to set email alerts
|

Human T-Cell Leukemia Virus (HTLV-I) Antibodies in Africa

Abstract: Antibodies specific for human T-cell leukemia-lymphoma virus type I (HTLV-I) were demonstrated in serum samples from various groups of people in South Africa, Uganda, Ghana, Nigeria, Tunisia, and Egypt. The samples had been collected for other purposes and were presumably selected without bias toward clinical conditions associated with HTLV infections. Regional differences in antibody positivity were observed, indicating widely distributed loci of occurrence of HTLV on the African continent in people of both b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
61
1
7

Year Published

1985
1985
1998
1998

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 214 publications
(71 citation statements)
references
References 20 publications
2
61
1
7
Order By: Relevance
“…Although a moderate number of ELISA reactors were found initially, only a small number were confirmed by the more specific western blot assay. The low prevalence of 0-9 % is in contrast to the 2 % prevalence previously reported from infectious disease clinic patients in Egypt [9], and lower than the rates in risk groups from endemic areas throughout the world. While HTLV-I does not appear to be a public health threat in Egypt, more surveys should be considered to monitor and further define the prevalence of this virus among populations at risk to infection.…”
Section: N T Constantine and Otherscontrasting
confidence: 65%
See 2 more Smart Citations
“…Although a moderate number of ELISA reactors were found initially, only a small number were confirmed by the more specific western blot assay. The low prevalence of 0-9 % is in contrast to the 2 % prevalence previously reported from infectious disease clinic patients in Egypt [9], and lower than the rates in risk groups from endemic areas throughout the world. While HTLV-I does not appear to be a public health threat in Egypt, more surveys should be considered to monitor and further define the prevalence of this virus among populations at risk to infection.…”
Section: N T Constantine and Otherscontrasting
confidence: 65%
“…Data indicated that 2 % of cases admitted to infectious disease clinics had antibodies to HTLV-I [9]. The prevalences in high-risk groups and normal individuals have not been determined.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In Trinidad/Tobago, HTLV-I infection is restricted largely to persons of African ancestry despite the fact that the population is equally divided between persons of Asian and African origin supporting the concept that the virus is endemic in Africa (Bartholomew et al, 1985). This hypothesis was supported by our previous case report of a Nigerian with classical adult T-cell leukaemia/lymphoma (Williams et al, 1984) and recent population surveys of HTLV-I in various locales of Africa (Fleming et al, 1982;Saxinger et al, 1984;Fleming et al, 1986;Williams et al, 1987). While the validity of the early HTLV-I serology in Africa has been questioned (Weiss et al, 1986) especially because of the remarkable discrepancy between the enzyme-linked screening and confirmatory assays when compared with the more sensitive Western immunoblot assay (Constantine et al, 1988;CDC, MMWR, 1988) .…”
supporting
confidence: 73%
“…These retroviruses are now known to be isolates of HLTV-I [52]. Sporadic occurrences of both HTLV-I and ATLL have been noted in many other areas of the world [10], and most recently parts of Africa have also been shown to be endemic [43].…”
Section: B Htl V -I and Adult T Cell Leukemia/ Lymphomamentioning
confidence: 99%